Unusual lesions seen in the caudals of the hadrosaur, Edmontosaurus annectens. Issue 3 (21st September 2022) - Anné, Jennifer; Whitney, Megan; Brocklehurst, Robert; Donnelly, Kevin; Rothschild, Bruce
Abstract: The study of pathologies in the fossil record allows for unique insights into the physiology, immunology, biomechanics, and daily life history of extinct organisms. This is especially important in organisms that have body structures dissimilar to those of extant organisms as well as transitional groups whose extant relatives may have very dissimilar physiologies. Comparisons between modern groups and their fossil ancestors are further complicated by the fact that fossil groups may have experienced unique biomechanical stresses as well as possessing a mixture of anatomical features seen in their related extant groups. In this study, we present lesions in the caudal vertebrae of the hadrosaur, Edmontosaurus annectens from the Ruth Mason Dinosaur Quarry of South Dakota, which exhibit unique morphologies. X‐ray microtomography was performed on the most extreme example of this morphology to allow for both a detailed and more accurate diagnosis of the pathologic condition as well as virtual conservation of the specimen. Based on the location, the overall morphology of the lesion, and the relative "normal" appearance of the internal microstructure, the most probable cause is postulated as long‐term biomechanical stresses exerted on this section of the tail by both lateral and dorsoventral motions of the tail. This deduction was based on a process of elimination for a variety of known osteological conditions; however, future work is needed to determine the nature of the stresses and why this condition has not been recorded in more hadrosaurian specimens.